Closed Course Performance Testing of a Work Zone Intrusion Alarm System. Issue 16 (December 2018) - Theiss, LuAnn; Lindheimer, Tomas; Ullman, Gerald L.
Oldcastle Materials, Inc. and ARTIS, LLC joined forces to develop an innovative work zone intrusion detection and alarm system. The alarm system flashes light-emitting diodes and emits an audible alarm if an intrusion is detected. Texas A&M Transportation Institute performed a closed course study to assess performance of the alarm system under conditions that may occur in real work zones. This testing was intended to verify that the alarm system does produce the proper alert when conditions warrant it and that alerts were not activated when conditions did not warrant them (i.e., that the system does not produce false alarms). Performance of the worker body alarms (designed to be worn by field personnel and activated when an intrusion threat is detected) was also evaluated. During testing, these devices were positioned at various locations to assess the ability of the system to correctly determine the location of the devices and their position relative to the intrusion threat. The alarm system was tested under two operating modes: lane closures and flagging operations. Several approach vehicle trajectories were used in both operating modes. The main alarm achieved a 100% success rate, whereas the worker body alarms achieved a 97% success rate. Unsuccessful events for the worker body alarms were attributable to the test protocol exceeding the effective communication range of the intrusion detection system. Ongoing improvements in the device are expected to significantly increase this communication range. All other device locations, scenarios, and trajectories tested achieved a 100% success rate.